Using ultrasonic investigations to develop anisotropic damage models for initially transverse isotropic materials undergoing damage to remain transverse isotropic. (1st May 2018) - Olsen-Kettle, Louise
Abstract: A severe limitation imposed by many continuum damage mechanics models is the assumption of initial isotropy in many anisotropic damage models. This may place unrealistic assumptions about the material being modelled or restrict the application of continuum damage mechanics to materials without significant anisotropy. It remains a challenge to use anisotropic continuum damage mechanics to model common rocks and materials with significant initial anisotropy, for example sedimentary rocks or brittle composite materials. We show how ultrasonic investigations in experiments where an initially transverse isotropic material undergoes damage-induced anisotropy can be used to guide the development of transverse isotropic damage models. We provide a robust way to validate and advance models of general anisotropic damage evolution based on continuum damage mechanics.